2017
DOI: 10.1007/s11910-017-0727-0
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Chameleons and Stroke Mimics in the Emergency Department

Abstract: The National Academy of Medicine has re-defined and highlighted the importance of diagnostic errors for patient safety. Recent rates of stroke under-diagnosis (false-negative cases, "stroke chameleons") range from 2-26% and 30-43% for stroke over-diagnosis (false-positive cases, "stroke mimics"). Failure to diagnosis stroke can preclude time-sensitive treatments and has been associated with poor outcomes. Strategies have been developed to improve detection of posterior circulation stroke syndromes, but ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 97 publications
2
55
2
4
Order By: Relevance
“…Misdiagnosis of acute stroke may result in worse patient functional outcomes due to failure to implement acute stroke interventions as well as standard processes of care [6]. Studies have reported that 2-26% of acute stroke presentations are misdiagnosed in the emergency department (ED) [5,[7][8][9][10]. Factors contributing to stroke misdiagnosis include non-specific or atypical symptoms [5,10], such as those associated with posterior circulation stroke (PCS) [8,10,11], decreased level of consciousness [9], younger patient age [8,9,12], lower cerebrovascular disease profile [8], and transient ischemic attack (TIA) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Misdiagnosis of acute stroke may result in worse patient functional outcomes due to failure to implement acute stroke interventions as well as standard processes of care [6]. Studies have reported that 2-26% of acute stroke presentations are misdiagnosed in the emergency department (ED) [5,[7][8][9][10]. Factors contributing to stroke misdiagnosis include non-specific or atypical symptoms [5,10], such as those associated with posterior circulation stroke (PCS) [8,10,11], decreased level of consciousness [9], younger patient age [8,9,12], lower cerebrovascular disease profile [8], and transient ischemic attack (TIA) [5].…”
Section: Introductionmentioning
confidence: 99%
“…220 Conditions like infections, migraine, seizures, syncope, vertigo, confusional states and functional symptoms are frequent stroke mimics. [221][222][223][224] Stroke mimics lead to costly hospital admissions and are stressful for the patients and their family. 225 Recognition of stroke mimics is therefore highly important, especially in an era with constant focus on shortening the time from hospital admission to administration of thrombolysis (door-to-needle time).…”
Section: Stroke Mimics After Incident Strokementioning
confidence: 99%
“…Stroke mimic patients represent up to 40% of all patients admitted with suspected stroke. 222 Many studies have observed that patients with stroke mimics have fewer ischemic stroke risk factors. 220,226,296,297 Prior studies have quantified the incidence of stoke mimics by reporting the proportions of stroke mimics in all suspected strokes in admitted to emergency departments or stroke units.…”
Section: Stroke Mimicsmentioning
confidence: 99%
“…Refieren que la paciente ha manifestado ideas de muerte y en la última semana presentó problemas familiares. alteracion del estado de conciencia, tener en cuenta, estudiar y descartar el accidente cerebrovascular (ACV) isquémico, ya que esta condición está descrita como uno de los principales síntomas camaleónicos, que son aquellas condiciones en donde un ACV puede simular una patología alternativa 16,17 . De los pacientes que ingresan con alteracion en el estado de conciencia sin evidencia de focalización, hasta en el 70% de los casos el diagnóstico de ACV no se realiza de forma correcta 18 .…”
Section: Caso Clínicounclassified
“…Por los síntomas y la presencia de ataxia, disartria con posterior alteración en el estado de conciencia, así como por el nistagmus vertical, era importante realizar RMN que es más sensible para evidenciar compromiso en fosa posterior 20 . Varios estudios han reportado que los síntomas camaleónicos del ACV son más probables en circulación posterior, siendo este compromiso el que más frecuentemente se pasa por alto y es mal diagnosticado en urgencias, por lo que es de vital importancia en los pacientes con este tipo de presentaciones realizar el examen físico completo con énfasis en el SNC y efectuar estudios con imágenes más avanzadas 16,21 .…”
Section: Caso Clínicounclassified